Sistem Informasi Perpustakaan Desa Pelawad Pintar (SIPP) Berbasis Web - Kristiyanto, Arip Kristiyanto (MULTINETICS, 2024)
Pelawad is one of the villages that already has a library called "Perpustakaan Desa Pelawad Pintar," but it has not been well managed. With the advancement of digital technology, it encourages people to work more effectively and efficiently. Pelawad Village Library still relies on manual methods to manage its data. This issue affects the effectiveness of library data management, including book data, borrowing records, return records, visitor or member data, and generating reports. By utilizing a web-based information system, the management of book data, member data, and library borrowing transactions can be more effective and efficient. This research aims to design a web-based information system using PHP programming language and MySQL database. The system development method employed is Extreme Programming (XP), black box testing dan user acceptance testing method is used for testing. The information system includes statistics with graphical information, the most read book titles, book categories that are frequently read, and members who borrow books the most. The test results user acceptance testing obtained a good score with a total score of 77.6%, a design category score of 78.6%, an efficient category score of 76% and a function category score of 76%.